FIRST YEAR MORTALITY AND MORBIDITY AFTER AMI IN PESHAWAR - Awan, Zahid Aslam; Mufti, Waqar (Journal of Ayub Medical College Abbottabad, 1996)
Two hundred and ten patients with acute myocardial infarction (AMI) were studied for mortality and morbidity in a tertiary hospital setting. Out of these, 117(56%) had anterior MI. 73(35%) had inferior MI, 12(6%) had non Q- wave MI, 8(4%) had lateral MI and 6(3%) had both interior and inferior MI. 134(64%;) received thrombolytic therapy. 37(18%) were diabetic and 33(16%) were hypertensive. 163(78%) could be followed for one year. The total first year mortality was 48(23%). The in- hospital mortality after AMI was 29(14%). Among those alive at the end of first year 90(71%) were in NYHA functional class I 28(22%;) in class II. 6(14%) in class III and 3(2%) in class IV.